Neutron capture cross section measurements for nuclear astrophysics at CERN n_TOF - Abbondanno, U. (2005)
A series of neutron capture cross section measurements of interest to nuclear astrophysics have been recently performed at n_TOF, the neutron spallation source operating at CERN. The low repetition frequency of the proton beam driver, the extremely high instantaneous neutron flux, and the low background conditions in the experimental area are optimal for capture cross section measurements on low-mass or radioactive samples. An overview of the measurements performed during the two experimental campaigns in 2002 and 2003 is presented with special emphasis on the measurement of the capture cross sections of the Os isotopes relevant for the cosmochronology based on the Re/Os clock.